Stress and mood states monitoring in a swimming team during a competitive period - Zanini, Gabriel de Souza [UNESP]; Filho, Dalton Müller Pessôa [UNESP]; Neiva, Cassiano Merussi [UNESP]; Da Silva, Daniel Pestana; Ciolac, Emmanuel Gomes [UNESP]; Verardi, Carlos Eduardo Lopes [UNESP] (My University, 2018)
The present study aims to identify and analyze stress levels, mood state, as well as the perception of stress and recovery of 32 athletes of both genders, swimmers. In order to quantitatively evaluate the variables the following instruments were used: the Recovery-Stress Questionnaire for Athletes (REST-Q) which describes the mental, emotional and physical well-being of the athletes, the Brunel Mood State Scale (BRUMS) which allows a rapid measurement of mood in populations composed by adults and adolescents and Foster Perception Subjective Effort (PSE) which aims to identify in a quick and simple way of how the practitioners of a certain activity comprises the effort accomplished during the proposed task. The results showed that in the first moments the athletes were in a high mood, which indicates an excellent performance for competitions, later it is possible to notice a reduction in the values of vigor and increase in the other variables, leading the athletes to an imbalance in the standard of the state of mood. Values obtained on the stress and recovery scale changed during the season, with stress indexes increased, while recovery values reduced, indicating susceptibility to injuries and overtire. In this way, the conclusion is that athletes have become more likely to have harmful and overtraining frames over time, thus it is necessary to monitor athlete workloads and perceptions. To better understanding, the states of mood it is necessary to know the athlete deeply and the context which he is present in.
Keywords: Mood state; Recovery; Sport; Stress